A new method to evaluate toxicological data reliability in risk assessments. (1st September 2019) - Bian, Qian; Ping, Yu; Jun, Wu; Lyu, Zhongming; Song, Yan; Zhang, Lei; Liu, Zhaoping
Highlights: A method named TRAM (Toxicological data Reliability Assessment Method) was developed to evaluate toxicological data reliability in food safety risk assessment in China. TRAM provides a transparent, easy-to-use and quantitative method for evaluating toxicological data quality. TRAM comprised 22 criteria for laboratory animal data, 15 for in vitro data, 12 for human data. TRAM uses 3 reliability categories: high(Quality score: 81-100 or met quick evaluation approach), moderate(60-80), low(<60). Abstract: Toxicological data used for risk assessments must undergo an evaluation of reliability. Nevertheless, a reliability evaluation scheme for such data has yet to be established in China. A method termed TRAM (Toxicological data Reliability Assessment Method) was developed to evaluate toxicological data reliability. A questionnaire survey was performed to identify the most important criteria for reliability, and was divided into three parts: laboratory animal data (LAD), in vitro data (IVD), and human data (HD). The criteria selected from the questionnaire survey and numerical score categorization finally reached a consensus after two conferences. TRAM comprises 22 criteria for LAD, 15 for IVD, and 12 for HD. Furthermore, a combination of a quick and detailed evaluation of approaches for LAD and IVD were proposed to improve evaluation efficiency. Different weights (1–4) were assigned to each criterion, and 0–4 points were allocated according to how well each criterion was met, then a Quality score was calculated. TRAM uses three reliability categories: high (Quality score: 81–100 or met a quick evaluation approach), moderate (60–80) and low(<60). TRAM provides a transparent, easy-to-use, and quantitative method for evaluating toxicological data reliability.